PENGEMBANGAN MEDIA ELEKTRONIK PADA PEMBELAJARAN IPA MATERI PEREDARAN DARAH MANUSIA - Nafisah, Nur Asfi; Rahayuni, Galuh; Dwiyanti, Aris Naeni (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
The purpose of this study is to develop and determine the feasibility of PEDAMALA (Human Circulatory with Song) electronic media as an effort to help deliver material. This research uses a type of Research and Development (R&D) research withÂ an ADDIE research model. Â There are 5 stages in this study, namely: Analysis, Design, Development, Implementation, andÂ Evaluation. Restrictions are carried out on the grounds that they are tailored to the needs of researchers, namely developing media and testing the feasibility of media. The data obtained are expert validation and teacher and student responses. The results showed: (1) media development begins with writing lyrics and creating songs, recording, drawing animations and making videos. (2) PEDAMALA electronic media obtained an assessment from media experts by 95% with very decent criteria, material experts by 91.7% with very decent criteria, linguists by 75% with decent criteria and music/song experts by 92.8% with very decent criteria. The implementation stage in the small group test was 93.5% with very feasible criteria, and the large group test was 9.5% with very feasible criteria